Awareness of conflict of interest as an academic standard of ethics - Lewicka-Strzałecka, Anna (Annales. Etyka w Życiu Gospodarczym, 2019)
The paper shows that conflicts of interest in science undermine its ethos. Some examples of this phenomenon have been analysed from the point of view of its destructive consequences. The need to counter them has also been identified in our country and some legal regulations and self-regulation are gradually being introduced. However, they are not always respected in practice. In the last part of the paper, a model of management of risk of bias in scientific research has been outlined. The main thesis says that an awareness of conflict of interest embracing both knowledge of the general issues and relevant assessment of the personal risk of lack of objectivism should be an ethical minimum of every scientific worker.